Pengaruh Kualitas Pelayanan Dan Varian Produk Terhadap Loyalitas Pelanggan Toko Kelontong - Ayudea Oktaviani; Sisca Septiani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to analyze the effect of Service Quality and Product Variants on Customer Loyalty at Darin Grocery Store in Cikopo Purwakarta. The source of the data in this study was obtained from a questionnaire (primary) which was distributed to the respondents. The population of this study were customers at the Darin Grocery Store in Cikopo Purwakarta. The research sample amount were 82 people. The research analysis method used is validity test, reliability test, multiple linear regression, f test and t test. The research findings indicate that the marketing strategy simultaneously affects customer loyalty. Based on multiple linear regression analysis, the coefficient of determination is 40.3%. The most dominant factor influencing is the product variance of the t test calculation. The t value for the service quality variable is 0.880, the t count for the product variant variable is 4.838. The results of the F test obtained F count of 26.715 and a significant value <0. 05.